ショウワ キチ ニ オケル EXOS-D ノ ジュシン ケイカク - 芳野, 赳夫; ヨシノ, タケオ; 福西, 浩; フクニシ, ヒロシ; Yoshino, Takeo; Fukunishi, Hiroshi (1985)
P(論文) 1989年, 極域超高層現象の探査を目的とした準極軌道科学衛星EXOS-Dが宇宙科学研究所によって打ち上げられる。これに伴い, 昭和基地でもこの衛星の観測データを直接テレメトリー受信し, 地上データとの同時観測を行うことが計画されている。本論文では遠地点10000kmの衛星と昭和基地間の回線設計を行い, これに基づき算出された直径10mのパラボラアンテナを, 実際に昭和基地に設置する場合の諸条件について考察を試みた。10mアンテナを昭和基地に設置することにより, 地球観測衛星LANDSAT, 海洋観測衛星MOSなどの多種目の衛星のデータ取得が可能となる。また, 超長基線干渉計(VLBI)として使用することによりプレート移動の精密測定も可能となるので, 今後の衛星による南極観測の研究範囲を多部門にわたり飛躍的に拡大させることができる。 The semi-polar orbital and the polar aeronomy observation satellite "EXOS-D", will be launched in February 1989 by the Institute of Space and Astronautical Science. The National Institute of Polar Research is planning to carry out coordinated ground and satellite observations by real-time EXOS-D data aquisition. In this paper, the size of a 10-meter dish which is determined by the results of the network analysis on the EXOS-D orbit data of 10000km apogee, and various technical conditions when it is constructed at Syowa Station are described. By the construction of this new 10-meter dish antenna at Syowa Station, it will become possible for us to track and observe not only the EXOS-D but also LANDSAT, MOS and other remote sensing satellites. And if it is used as one point in a VLBI system, a precise measurement of the global continental drift will be made. departmental bulletin paper